Contextualizing Disaster - Button, Gregory V.; Schuller, Mark (Berghahn Books, 2016)
"Contextualizing Disaster" offers a comparative analysis of six recent highly visible disasters and several slow-burning, hidden, crises that include typhoons, tsunamis, earthquakes, chemical spills, and the unfolding consequences of rising seas and climate change. The book argues that, while disasters are increasingly represented by the media as unique, exceptional, newsworthy events, it is a mistake to think of disasters as isolated or discrete occurrences. Rather, building on insights developed by political ecologists, this book makes a compelling argument for understanding disasters as transnational and global phenomena.